Penggunaan Web Baggage Central Tracking Citilink (BCTC) Untuk Menangani Irregularity Property Pada Maskapai Citilink di Bandar Udara Internasional - Nurdewi Murtivia; Herida Panji Olivia Azhar (Student Scientific Creativity Journal, 2023)
PT Citilink or Citilink Indonesia is a subsidiary of the Garuda Indonesia (Persero) company. This airline uses a low-cost flight system or Low Cost Carrier (LCC) with Lost and Found Services related to handling passenger luggage on Citilink airlines, but many people don't know about it. part of the baggage handling itself, one of which is the use of Citilink's Web Baggage Central Tracking (BCTC), in handling Irregularity Property. The purpose of this research is to find out the use of the BCTC web in handling Irregularity Property in the Lost and Found unit at Yogyakarta International Airport and to find out the obstacles faced in using the BCTC web in handling Irregularity Property in the Lost and Found unit at Yogyakarta International Airport.This study used descriptive qualitative method. This research was carried out on April 1– April 20 2023 at Citilink Airlines, Yogyakarta Kulon Progo International Airport, Citilink Airlines, Yogyakarta Kulon Progo International Airport. The data collection techniques used in this research were documentation, observation and interviews with Lost and Found unit officers at Yogyakarta International Airport. Data analysis techniques use data reduction, data presentation, and drawing conclusions.The results of the research show that in handling baggage damage, passengers who experience property irregularities can report it to the relevant officers or make a report on Citilink's official BCTC website to get further action in accordance with Citilink airline's standard operating procedures for handling baggage damage. and baggage damage is handled within 14 days from receipt of the complaint submitted by the passenger to the airline. Obstacles in using the BCTC Web to handle Irregularity Property at the Lost and Found unit of Yogyakarta International Airport include technical problems, coordination with airlines, the need for adequate resources, and increasing passenger volume. The proposed solution includes intensive training, formation of a technical team, development of collaboration protocols, adequate budget allocation, and proper growth planning.